PENGARUH SEKOLAH RAMAH ANAK TERHADAP PERILAKU ASOSIAL - Supriadi Torro; Dyan Paramitha Darmayanti; Nurmagfirah Nurmagfirah (Social Landscape Journal, 2022)
This study aims to determine 1) the description of the implementation of child-friendly schools, 2) the effect of child-friendly school programs on ansocial behavior. This type of research is quantitative with a population of 361 people. The research sample was taken using a random sampling technique with a total sample of 41 people. Data collection is done through questionnaires and documentation. Data analysis using descriptive and inferential techniques using SPSS version 24. The results of the study show that the friendly school program has provided space for students to avoid violence at school. This can be seen in the availability of shared reading rooms, open play areas. In addition, the research results also illustrate that variable X (child-friendly school programs) has a significant and very strong influence on variable Y (ansocial behavior). This is indicated by a significance value of 0.002 <0.05, meaning that there is a significant relationship and a coefficient value of 0.838 which indicates a very strong relationship. In addition, for variable X, the tcount value is 1.748. Where the number is > 1.685 then H0 is rejected and H1 is accepted. Programs from child-friendly schools that support extracurricular activities can attract students to actively participate in positive activities carried out by the school. So as to minimize the occurrence of anti-social actions, violence or bullying in the school environment, because students will be preoccupied with activities that simultaneously stimulate high social values.